The Bees of the Genus Colletes (Hymenoptera: Apoidea: Colletidae) from China - Niu, Ze-Qing; Zhu, Chao-Dong; Kuhlmann, Michael (Zootaxa, 2014)
Available information about the bees of the genus Colletes from China is summarized. Currently, 66 species are recorded from China, of which two species, Colletes linzhiensis sp. nov. and C. spinatus sp. nov., are described as new. Type specimens are deposited in the Insect Collection of the Institute of Zoology, Chinese Academy of Sciences, Beijing, China. Thirteen species are recorded for China for the first time: C. edentuloides Kuhlmann, 2011, C. pauljohni Kuhlmann, 2002, C. tuberculatus Morawitz, 1894, C. annapurnensis Kuhlmann, 2002, C. laevigena Noskiewicz, 1936, C. annejohnae Kuhlmann, 2003, C. eous Morice, 1904, C. squamosus Morawitz, 1879, C. wollmanni Noskiewicz, 1936, C. bhutanicus Kuhlmann, 2003, C. kaszabi Kuhlmann, 2002, C. uralensis Noskiewicz, 1936, and C. dorni Kuhlmann, 2002. The male of C. edentuloides Kuhlmann, 2011 and the female of C. pseudolaevigena Kuhlmann, 2002 are described for the first time. Colletes dudgeonii Bingham, 1897 was erroneously recorded from China and is removed from the list of Chinese species.